Development Approach of Government Organization Administration for Supporting Pracharath Market in Nakhonpathom Province - Chooket, Jiranan; Thamma-apipon, Sawanya (Journal of Innovation and Management, 2020)
This research was to study administration and development the problems of government administration organization for Pracharath Market in Nakhonpathom province. Also, to studying of supporting government organization in Pracharath Market in Nakhonpathom province. This study was a qualitative research by in – depth interview semi-structured interview and structured interview The samples of the group study were 17 person who are entrepreneurs, customers and represent an organization and non-participant observation. The data were collected, analyzed and concluded and presented descriptive research results by methodological triangulation. The findings showed that the problems of government administration organization for Pracharath Market in Nakhonpathom province have 8 main factors to developing: (1) Planning- the meeting was set up to determine both district and province, (2) Organization - there was set up department, district and province but was not clearly set up committee of marketing, (3) Staffing – Nobody was selected or recruitment who was specialist, (4) Directing – There was organized commands from high to below both formal command and informal command, (5) Coordinating – there was cooperated both inside and outside organization as well as it was written and verbal, (6) Reporting – there was reported documents both department and province, (7) Budgeting – Community Development Department gave budget, and (8) Innovation – using it for communication and public relations. Furthermore, the supporting of government organization by Community Development Departmet are divided in 2 factors 1.To support budget for materials and public relations. 2. To support in public relations Pracharath Market public relations.